Contrasting Ecological Processes and Functional Compositions Between Intestinal Bacterial Community in Healthy and Diseased Shrimp - Zhu, Jinyong; Dai, Wenfang; Qiu, Qiongfen; Dong, Chunming; Zhang, Jinjie; Xiong, Jinbo (Microbial ecology, 2016)
Intestinal bacterial communities play a pivotal role in promoting host health; therefore, the disruption of intestinal bacterial homeostasis could result in disease. However, the effect of the occurrences of disease on intestinal bacterial community assembly remains unclear. To address this gap, we compared the multifaceted ecological differences in maintaining intestinal bacterial community assembly between healthy and diseased shrimps. The neutral model analysis shows that the relative importance of neutral processes decreases when disease occurs. This pattern is further corroborated by the ecosphere null model, revealing that the bacterial community assembly of diseased samples is dominated by stochastic processes. In addition, the occurrence of shrimp disease reduces the complexity and cooperative activities of species-to-species interactions. The keystone taxa affiliated with Alphapro teobacteria and Actinobacteria in healthy shrimp gut shift to Gammaproteobacteria species in diseased shrimp. Changes in intestinal bacterial communities significantly alter biological functions in shrimp. Within a given metabolic pathway, the pattern of enrichment or decrease between healthy and deceased shrimp is correlated with its functional effects. We propose that stressed shrimp are more prone to invasion by alien strains (evidenced by more stochastic assembly and higher migration rate in diseased shrimp), which, in turn, disrupts the cooperative activity among resident species. These findings greatly aid our understanding of the underlying mechanisms that govern shrimp intestinal community assembly between health statuses.